Effect of concept mapping strategy in teaching-learning economics at higher classes (European journal of volunteering and community-based projects, 2020)
Economics can be taught and learn better using different teaching strategies. Concept mapping is one among others in teaching-learning economics. This study aim to investigate the effect of using concept mapping in teaching-learning economics. The study was carried out in XI Arts at one higher secondary school under Thimphu Tromde, with 35 students. The study was a mixed method. The quantitative data was collected through autumn class test (pre-test) and class test (post-test). The pretest and post-test data were analyzed and interpreted using descriptive statistics via mean, standard deviation, and inferential statistics via t-test and level of confidence and statistical significance. The qualitative data collected though observation of group works and presentation, and group reflective journal were analyzed by coding and thematic analysis was drawn to analyze the data. The findings showed concept mapping is effective in teaching-learning economics and students has positive opinion towards concept mapping usage. Concept mapping help students to understand and remember economic concepts and enhances descriptive ability. Students also said that the use of concept mapping build confidence to participate in the classroom and enhanced long-term retention power. However, the finding also revealed that all economic lessons cannot be taught through concepts mapping.